Saint George as Cultural Unifier: Visual Clues in Carpaccio’s Cycle at the Scuola Dalmata in Venice - Barker, Alison C. (Confraternitas)

(untitled) (Iter Press, 2021)
Late medieval Venetians had an established tradition of visualising Saint George and venerating him in many ways and for differing purposes, but he was also celebrated by non-Venetians living in the city. The diasporic community of the Schiavoni chose the saint to be the patron of their confraternity (Scuola), and so he features prominently in the decorative programmes they commissioned for their building; this decision had its origins in their provenance, occupations, and local affinity with the Venetians. This article has two aims: first, to chart the backgrounds of the Schiavoni confratelli, and second, to examine the visual clues within Carpaccio’s narrative cycle at the Scuola Dalmata to explore themes of unity, mobility, and otherness. It will conclude that the confratelli’s background of home-displacement, and their military, mercantile, and artisan occupations led to their selection of Saint George as patron; and that their attempts to integrate into the Venetian community can be understood in conversation with the iconography of the Saint George narrative on the walls of their Scuola.